2015
DOI: 10.1037/cou0000113
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association of depression with career indecisiveness, career-decision status, and career-preference crystallization.

Abstract: Depression has detrimental effects on broad areas of functioning. However, its association with career decision-making factors has been largely unexplored. In the present study, we focused on the association between career decision-making difficulties, career-decision status, and career-preference crystallization, on the one hand, and depression, on the other. The hypothesis that high levels of career decision-making difficulties, less advanced decision status, and low levels of preference crystallization are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
(129 reference statements)
1
26
1
Order By: Relevance
“…In another study examining gender roles and career decision‐making, Turkish high school students with androgynous roles had greater career decision‐making self‐efficacy (Bolat & Odaci, 2017). In Gadassi et al (2015), women were more likely than men to experience lack of crystallization of career preference and related depressive symptoms. However, female students were more subjective to the effectiveness of workshops on reducing perceived gender restraints (Hechtlinger & Gati, 2019).…”
Section: Influences On Career Decision‐making and Cdsementioning
confidence: 95%
“…In another study examining gender roles and career decision‐making, Turkish high school students with androgynous roles had greater career decision‐making self‐efficacy (Bolat & Odaci, 2017). In Gadassi et al (2015), women were more likely than men to experience lack of crystallization of career preference and related depressive symptoms. However, female students were more subjective to the effectiveness of workshops on reducing perceived gender restraints (Hechtlinger & Gati, 2019).…”
Section: Influences On Career Decision‐making and Cdsementioning
confidence: 95%
“…Examining career decision-making self-efficacy and career choice anxiety can provide more insight into the career decision-making process. People with high self-efficacy for career decision-making can develop career plans effectively, but those with a high level of career choice anxiety may experience difficulties in the career decision-making process ( Germeijs et al, 2006 ). In other words, those with high career decision-making efficacy can make successful career decisions and perform successfully in their careers whereas those with high career choice anxiety may experience negative outcomes in career decision-making and career performance as they are overwhelmed by the career decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…An individual’s affective state can be the key to understanding the appropriate career intervention plan in the career-counseling domain ( Hirschi and Freund, 2014 ). In particular, Germeijs et al (2006) argued that a diary-based approach is needed rather than a questionnaire response in order to fully understand the career decision process and to address the limitations of their longitudinal study. However, to our knowledge, no study has been conducted to investigate the fluctuations in career decision attitudes such as career decision-making self-efficacy and career choice anxiety on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review investigating the prevalence of burnout among healthcare professionals in the Arab world reported high levels of burnout among nurses compared to other healthcare professionals suggesting that nurses are at a high risk of developing burnout in this region ( 23 ). Another study explored the role of depression on career choice among different professionals including nursing and found that perceived self-concept and identity-related career decision-making difficulties were associated with depressive symptoms for both men and women ( 24 ). Previous research has highlighted the importance of career counseling to help students match their skills to ease anxiety and improve their self-efficacy ( 25 – 27 ).…”
Section: Introductionmentioning
confidence: 99%